2007
DOI: 10.1074/jbc.m700732200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Up-regulation of Inhibitory PAS Domain Protein Gene Expression by Hypoxia-inducible Factor 1 (HIF-1)

Abstract: The inhibitory PAS (Per/Arnt/Sim) domain protein (IPAS), a dominant negative regulator of hypoxia-inducible transcription factors (HIFs), is potentially implicated in negative regulation of angiogenesis in such tissues as the avascular cornea of the eye. We have previously shown IPAS mRNA expression is up-regulated in hypoxic tissues, which at least in part involves hypoxiadependent alternative splicing of the transcripts from the IPAS/ HIF-3␣ locus. In the present study, we demonstrate that a hypoxia-driven t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 42 publications
5
80
1
1
Order By: Relevance
“…Pasanen et al (21) demonstrated that HIF-3α2 and HIF-3α4 are inducible during hypoxia and the inductions require HIF-1α. A similar previous study revealed that HIF-1α binds to the hypoxia response element (HRE) in the IPAS promoter and induces the expression of IPAS (36). However, the stabilized form of HIF-1α does not affect the mRNA expression levels of HIF-3α in zebrafish embryos (35) and 3T3-L1 cells (37).…”
Section: Regulation Of Hif-3α Expression At the Transcriptional Levelmentioning
confidence: 97%
See 3 more Smart Citations
“…Pasanen et al (21) demonstrated that HIF-3α2 and HIF-3α4 are inducible during hypoxia and the inductions require HIF-1α. A similar previous study revealed that HIF-1α binds to the hypoxia response element (HRE) in the IPAS promoter and induces the expression of IPAS (36). However, the stabilized form of HIF-1α does not affect the mRNA expression levels of HIF-3α in zebrafish embryos (35) and 3T3-L1 cells (37).…”
Section: Regulation Of Hif-3α Expression At the Transcriptional Levelmentioning
confidence: 97%
“…At first, HIF-1α binds to the HRE in the IPAS promoter and induces the expression of IPAS (36). Increased levels of IPAS dimerize with HIF-1α protein and inhibits further induction of IPAS (36). In hepatoma cells, ectopic expression of IPAS decreases the expression of vascular endothelial growth factor (VEGF), resulting in reduced tumor growth and decreased tumor vascular density in vivo (27).…”
Section: Biological Functions Of Hif-3mentioning
confidence: 99%
See 2 more Smart Citations
“…The IPAS-specific splicing product of the HIF-3 locus is hypoxia-inducible and 8 HIF-1 binds to the hypoxia-responsive cis-element of the IPAS promoter representing a classic negative feedback that restricts HIF-mediated gene expression in hypoxia (Figure 2A) [39,41]. Interestingly, however, the IPAS-specific mRNA splicing was still observed in the absence of the HIF-1-binding site of the IPAS promoter indicating that HIF-independent factors may also be involved in the production of the dominant negative isoform [41]. The uncoupled nature of IPAS expression and splicing suggest additional control mechanisms in this regulation.…”
Section: Transcriptional Feedbackmentioning
confidence: 99%